Designing Learning Centres that Facilitate Knowledge Construction on Science Process Skills in Early Childhood Classrooms - Pakombwele , Agnes; Tsakeni, Maria (Journal of Ecohumanism, 2024)
Science education is perceived to have the potential to develop 21st century competencies. In Zimbabwe, the teaching of science in early childhood by using learning centres is considered as a way of empowering young learners with scientific knowledge and skills to become productive citizens in future. To strengthen the initiative, resources are being channelled and policies crafted to support the teaching of STEM (science, technology, engineering and mathematics). Despite considerable efforts to introduce STEM in early childhood development (ECD), research concerning the benefits of developing science skills using learning centres is sparse. This study adopted an interpretive paradigm and multiple case study design for three schools and three purposively selected ECD teachers. Data was solicited through semi-structured interviews, document analysis and classroom observations. The variable nature of learning centres in ECD classrooms is an indication of shortcomings in policy on teaching using learning centres. At learning centres, learners construct scientific knowledge, ideas and skills through interaction with peers and developmentally appropriate materials. Teachers should be creative and innovative and create learning centres that enable learners to explore the world and construct scientific knowledge through active participation and sharing ideas. A policy to guide the teachers on constructing appropriate learning centres for effective teaching of science skills should be drafted.